2005
DOI: 10.1016/j.jtcvs.2004.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and sutureless techniques for management of the pulmonary veins: Evolution of indications from postrepair pulmonary vein stenosis to primary pulmonary vein anomalies

Abstract: The sutureless technique for postrepair pulmonary vein stenosis is associated with encouraging midterm results. Extension of the indications for the technique to primary repair appears safe with the development of simple intraoperative maneuvers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
1
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(103 citation statements)
references
References 14 publications
1
90
1
11
Order By: Relevance
“…It also is probable that reoperation rates have increased commensurate with the increase in the number and level of complex repairs undertaken in the recent era and a concomitant decrease in the threshold for reintervention. Sutureless techniques for recurrent PVO as described by our group 23,24 and others 25 have demonstrated superior outcomes over conventional surgical (eg, pulmonary venous endarterectomy or patch enlargement) and catheter-based methods. 25,26 A recent study from our institution 24 reported acceptable freedom from death and reoperation with extension of the sutureless technique to patients with primary pulmonary venous anomalies.…”
Section: Reoperationmentioning
confidence: 94%
See 1 more Smart Citation
“…It also is probable that reoperation rates have increased commensurate with the increase in the number and level of complex repairs undertaken in the recent era and a concomitant decrease in the threshold for reintervention. Sutureless techniques for recurrent PVO as described by our group 23,24 and others 25 have demonstrated superior outcomes over conventional surgical (eg, pulmonary venous endarterectomy or patch enlargement) and catheter-based methods. 25,26 A recent study from our institution 24 reported acceptable freedom from death and reoperation with extension of the sutureless technique to patients with primary pulmonary venous anomalies.…”
Section: Reoperationmentioning
confidence: 94%
“…Sutureless techniques for recurrent PVO as described by our group 23,24 and others 25 have demonstrated superior outcomes over conventional surgical (eg, pulmonary venous endarterectomy or patch enlargement) and catheter-based methods. 25,26 A recent study from our institution 24 reported acceptable freedom from death and reoperation with extension of the sutureless technique to patients with primary pulmonary venous anomalies. Further studies are needed to determine the utility of novel techniques in the heterogeneous spectrum of TAPVC.…”
Section: Reoperationmentioning
confidence: 94%
“…A technique by which the pericardium around the pulmonary veins is attached to the left atrium avoids any stitches in the cut edges of the pulmonary veins and is now considered the best approach. [27][28][29] Limited experience suggests that this sutureless marsupialization may be superior to previous approaches that used direct anastomosis after resection of stenotic segments or patching of the stenotic veins. Overall, freedom from reoperation or death at 5 years, however, is still only Ϸ50%.…”
Section: Treatment and Prognosis Of Pediatric Pulmonary Vein Stenosismentioning
confidence: 99%
“…Overall, freedom from reoperation or death at 5 years, however, is still only Ϸ50%. 28,29 Patients with milder degrees of stenosis and stenosis of only 1 or 2 pulmonary veins clearly have a better prognosis. Progressive pulmonary vein stenosis isolated to 1 lung may be survivable even though flow studies demonstrate little or no flow to the involved lung.…”
Section: Treatment and Prognosis Of Pediatric Pulmonary Vein Stenosismentioning
confidence: 99%
“…The purpose of this approach is to reduce trauma to the pulmonary veins by reducing any stimulus for the regrowth of obstructive tissue (2). Unfortunately, the five-year survival and reoperation-free rate is only 50% (10,12). Other surgical interventions include balloon dilation and stent insertion (2).…”
Section: Discussionmentioning
confidence: 99%